Magnetron sputtering of carbon supersaturated tungsten films – A chemical approach to increase strength. (October 2021) - Fritze, S.; Chen, M.; Riekehr, L.; Osinger, B.; Sortica, M.A.; Srinath, A.; Menon, A.S.; Lewin, E.; Primetzhofer, D.; Wheeler, J.M.; Jansson, U.
Graphical abstract: Highlights: W:C thin films with bcc structure have been deposited by magnetron sputtering. X-ray and electron diffraction measurements suggest the formation of supersaturated W:C solid solution phases. The carbon supersaturated solid solution films have enhanced properties. The carbon supersaturated bcc solid solution sample is ∼24 GPa hard. Abstract: Tungsten (W)-based materials attract significant attention due to their superior mechanical properties. Here, we present a chemical approach based on the addition of carbon (C) for increased strength via the combination of three strengthening mechanisms in W thin films. W:C thin films with C concentrations up to 4 at.% were deposited by magnetron sputtering. All films exhibit a body-centred-cubic structure with strong texture and columnar growth behaviour. X-ray and electron diffraction measurements suggest the formation of supersaturated W:C solid solution phases. The addition of C reduced the average column width from 133 nm for W to 20 nm for the film containing 4 at.% C. The column refinement is explained by a mechanism where C acts as re-nucleation sites. The W film is 13 GPa hard, while the W:C films achieve a peak hardness of 24 GPa. The W:C films are 11 GPa harder than the W film, which is explained by a combination of grain refinement strengthening, solid solution strengthening and increased dislocation density. Additional micropillar compression tests showed that the flow stress increased upon C addition, from 3.8 to 8.3 GPa and no brittle fracture was observed.